Estimating the relative rates of lipopolysaccharide synthesis in Escherichia coli K-12 by click chemistry-mediated labeling - Sheng Shu; Wei Mi (PLoS ONE, 2025)
Lipopolysaccharide (LPS), a critical glycolipid component of Gram-negative bacteria, plays a central role in bacterial membrane integrity and host immune interactions. Despite extensive studies on the regulation of LPS synthesis, methods to quantify its synthesis rate remain limited. Here, we present a novel approach to measure in vivo LPS synthesis rates in the E. coli K-12 strain MG1655 using click chemistry. This method involves the incorporation of an exogenous Kdo analog, 8-azido-3,8-dideoxy-D-manno-oct-2-ulosonic acid (Kdo-N3), into newly synthesized LPS, followed by a copper-free click reaction with a fluorescent alkyne. The labeled LPS is separated by SDS-PAGE and visualized via in-gel fluorescence. We compared two fluorescent dyes and found that AZDye 488 DBCO exhibited stronger sensitivity for labeling LPS during the log phase of bacterial growth. Our results further demonstrated that the amount of newly synthesized LPS correlates linearly with the pulse labeling time of Kdo-N3, validating this approach as a reliable method for estimating relative LPS synthesis rates during the exponential phase of E. coli MG1655 growth. This method offers a reliable, non-radioactive approach for measuring LPS synthesis in vivo, providing a powerful tool to investigate bacterial physiology and the regulation of LPS biogenesis.